1992
DOI: 10.1128/jcm.30.2.396-400.1992
|View full text |Cite
|
Sign up to set email alerts
|

Clinical illnesses associated with isolation of dysgonic fermenter 3 from stool samples

Abstract: The clinical significance of the fastidious organism DF-3 isolated from stool cultures is unclear. We sought to improve our understanding of this organism and to further define its association with human disease. Stool cultures for DF-3 were obtained from three sources: an ongoing study of enteric pathogens in patients infected with the human immunodeficiency virus, a screening procedure in which all stool samples submitted for Clostridium difficile toxin assay were cultured for DF-3, and stool samples submitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Metabolic fatty acids produced by the blood isolate were propionic, lactic, and succinic acids, and the major cellular fatty acids were a-C 15:0 (26%), i-3-OH-C 16:0 (21%), i-C 14:0 (13%), 3-OH-C 16:0 (6%), C 16:0 (5%), i-C 15:0 (4%), C 15:0 (3%), C 16:17c (3%), and C 18:19c (3%). In line with previous results (1,2,4), the blood isolate was susceptible to amoxicillin-clavulanate, clindamycin, erythromycin, piperacillin-tazobactam, rifampin, tetracycline, and trimethoprim-sulfamethoxazole (Table 1). Pulsed-field gel electrophoresis did not reveal visible bands in any run.…”
supporting
confidence: 91%
“…Metabolic fatty acids produced by the blood isolate were propionic, lactic, and succinic acids, and the major cellular fatty acids were a-C 15:0 (26%), i-3-OH-C 16:0 (21%), i-C 14:0 (13%), 3-OH-C 16:0 (6%), C 16:0 (5%), i-C 15:0 (4%), C 15:0 (3%), C 16:17c (3%), and C 18:19c (3%). In line with previous results (1,2,4), the blood isolate was susceptible to amoxicillin-clavulanate, clindamycin, erythromycin, piperacillin-tazobactam, rifampin, tetracycline, and trimethoprim-sulfamethoxazole (Table 1). Pulsed-field gel electrophoresis did not reveal visible bands in any run.…”
supporting
confidence: 91%
“…DF‐3 microorganisms are particularly resistant to antimicrobials, and almost uniform resistance has been described to aminoglycosides, quinolones and all β‐lactams, except for imipenem, which showed variable activity [6,7]. In our case both imipenem and meropenem showed MICs >32 mg/L by E‐test (AB Biodisk.…”
Section: Biochemical Characteristics Of Our Isolatementioning
confidence: 66%
“…DF‐3 has recently been associated with human disease, mainly chronic diarrhea [6–9]. We were able to find 10 cases of diarrhea purportedly caused by DF‐3.…”
Section: Biochemical Characteristics Of Our Isolatementioning
confidence: 96%
See 1 more Smart Citation
“…Hickling et al (144) reviewed 41 cases of DF-2 infection and noted five cases of cancer: three cases of Hodgkin's disease and two cases of chronic lymphocytic leukemia. There appears to The unnamed Capnocytophaga species called DF-3 has been shown in some studies (25,118,311) to be associated with gastrointestinal disease. Gill et al (118) showed that 1.6% (11 of 690 cultures) of stool cultures were positive for DF-3.…”
Section: Capnocytophaga Sppmentioning
confidence: 99%